(3QjGOI GdCYeGd GdELJeGYjIs - (3GdMfjWj(B, (3gjKe Ndas ((3YeGfs (3OGQ GdeSjQI ddfTQ hGdJhRjYs, 2021)
(3GdJWhQ GdJGQjNj dQjGOI GdCYeGd GdGLJeGYjI, GdQjGOjhf GdGLJeGYjhf, NUGFU QjGOI GdCYeGd, QjGOI GdCYeGd GdGLJeGYjI, NUGFU QjGOI GdCYeGd GdGLJeGYjI, QCS GdeGd GdGLJeGYj, eHGOF GdQjGOI GdGLJeGYjI, GdeDSSI GdGLJeGYjI GdQjGOjI, GdeTGQjY GdGLJeGYjI, CSS heaGgje GdQjGOI GdGLJeGYjI, GdeDSSGJ GdGLJeGYjI GdQjGOjI, hXGFa GdQjGOI GdGLJeGYjI, CSHGH hOhGaY GdQjGOI GdGLJeGYjI, GdeTGQjY GdGLJeGYjI, eaghe GdeTQhY GdGLJeGYj, ChdhjI CYeGd GdeDSSI GdGLJeGYjI GdQjGOjI hegeJgG GdQFjSI hGdCgOGa , CfhGY GdeDSSGJ GdGLJeGYjI, GdOhQ GdQjGOj dQjGOI GdCYeGd GdGLJeGYjI, GdCgOGa GdGLJeGYjI ZjQ GdQHMjI, Gdeaghe GdfXQj dQjGOI GdCYeGd GdGLJeGYjI, Gdeaghe GdYedj dQjGOI GdCYeGd GdGLJeGYjI, GdefXeGJ ZjQ GdQHMjI, GdefXhQ GdYGe ddQjGOI GdGLJeGYjI, efXhQ Ndb GdbjeI GdGLJeGYjI, efXhQ QHMH hZjQ QHMj, GdGHJcGQ aj QjGOI GdCYeGd GdGLJeGYjI, GdGHJcGQ GdGLJeGYj hGdJZjjQ GdGLJeGYj, GdefgL GdQjGOj GdGLJeGYj, efGgL GdJYdje GdLGeYj dQjGOI GdCYeGd GdGLJeGYjI, efgL QjGOI GdCYeGd GdGLJeGYjI, JOQjH QjGOI GdCYeGd GdGLJeGYjI, YedjI QjGOI GdCYeGd GdGLJeGYjI, efXeI GdQjGOI GdGLJeGYjI, ehGAeI egeI hGSJQGJjLjI GdQjGOI GdGLJeGYjI eY GdefXeGJ, JCSjS GdeTQhY GdQjGOj GdGLJeGYj, GdGHJcGQGJ aj GdefXeI GdQjGOjI GdGLJeGYjI, JNWjW hJfajP eTGQjY GdQjGOI GdGLJeGYjI, GdCgOGa GdYGeI dHQGeL QjGOI GdCYeGd GdGLJeGYjI, CgOGa JYdje HQGeL QjGOI GdCYeGd GdGLJeGYjI, CSS heHGOF Jchjf GdeTGQjY GdQjGOjI GdGLJeGYjI, efgLjGJ hCfXeI QjGOI GdCYeGd , QCS GdeGd GdHTQj aj feGPL QjGOI GdCYeGd GdQjGOjI, CSHGH hOhGaY GdQjGOI GdGLJeGYjI, WHjYI QjGOI GdCYeGd GdGLJeGYjI, Ndb GdbjeI GdGLJeGYjI, OQGSGJ MGdGJ QjGOjI GLJeGYjI hefGbTI GdCSHGH hGdOhGaY, GdCSHGH GdOGaYI dQjGOI GdCYeGd GdGLJeGYjI, QCS GdeGd GdGLJeGYj hGdTHcGJ GdQjGOjI, GdQjGOI GdGLJeGYjI hGdJMhd GdeLJeYj, WHjYI GdGHJcGQGJ GdGLJeGYjI, NUGFU GdefXeGJ GdGLJeGYjI(B.s
Keywords: (3EOGQI GdCYeGds; (3GdNOeI GdELJeGYjIs